Thermoelectric–pyroelectric hybrid energy generation from thermopower waves in core–shell structured carbon nanotube–PZT nanocomposites. (4th January 2017) - Yeo, Taehan; Hwang, Hayoung; Shin, Dongjoon; Seo, Byungseok; Choi, Wonjoon
Abstract: There is an urgent need to develop a suitable energy source owing to the rapid development of various innovative devices using micro-nanotechnology. The thermopower wave (TW), which produces a high specific power during the combustion of solid fuel inside micro-nanostructure materials, is a unique energy source for unusual platforms that cannot use conventional energy sources. Here, we report on the significant enhancement of hybrid energy generation of pyroelectrics and thermoelectrics from TWs in carbon nanotube (CNT)–PZT (lead zirconate titanate, P(Z0.5 –T0.5 )) composites for the first time. Conventional TWs use only charge carrier transport driven by the temperature gradient along the core materials to produce voltage. In this study, a core–shell structure of CNTs–PZTs was prepared to utilize both the temperature gradient along the core material (thermoelectrics) and the dynamic change in the temperature of the shell structure (pyroelectrics) induced by TWs. The dual mechanism of energy generation in CNT–PZT composites amplified the average peak and duration of the voltage up to 403 mV and 612 ms, respectively, by a factor of 2 and 60 times those for the composites without a PZT layer. Furthermore, dynamic voltage measurements and structural analysis in repetitive TWs confirmed that CNT–PZT composites maintain the original performance in multiple TWs, which improves the reusability of materials. The advanced TWs obtained by the application of a PZT layer as a pyroelectric material contributes to the extension of the usable energy portion as well as the development of TW-based operating devices.